Renewal and resurgence of severe problem behavior in an intensive outpatient setting: Prevalence, magnitude, and implications for practice. (24th March 2022) - Falligant, John M.; Chin, Michelle D.; Kurtz, Patricia F.
Abstract: Following successful behavioral treatment in which problem behavior is reduced, problem behavior sometimes reemerges as a function of changes in stimulus conditions (i.e., renewal) or the worsening of reinforcement conditions for an appropriate alternative response (i.e., resurgence). Extant research suggests that both renewal and resurgence may be relatively prevalent phenomenon in a variety of clinical settings. The purpose of the present study was to replicate and extend extant research quantifying the prevalence and magnitude of renewal (Experiment 1) and resurgence (Experiment 2) in an intensive outpatient clinic via retrospective consecutive controlled case series (CCCS; Hagopian, 2020). Findings from the current study—which represents the largest sample to date investigating relapse in applied settings—suggest that both renewal and resurgence are relatively common phenomenon and occur in the majority of treatment applications. Based on our findings (and emerging research in this area), we provide recommendations for practitioners to mitigate the occurrence of renewal and resurgence in clinical contexts.